2009
DOI: 10.1152/ajplung.00063.2009
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of stromal interaction molecule 1 attenuates store-operated Ca2+ entry and Ca2+ responses to acute hypoxia in pulmonary arterial smooth muscle

Abstract: from an EF-hand motif in the NH 2 -terminal region of STIM1 located within the SR/ER lumen, translocation of STIM1 proteins to form oligomeric collections termed "puncta" in portions of the SR/ER membrane close to SOC in plasma membrane, and interactions of STIM1 with SOC and/or associated regulatory proteins that lead to channel activation and SOCE (13,59,62). Indeed, it has been proposed that fulfillment of these functions by STIM1 should define SOC (58). Closely related to STIM1 is STIM2, a 105-kDa protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 64 publications
(98 reference statements)
3
66
1
2
Order By: Relevance
“…Interestingly, even though the silencing efficiency was of between 65 and 80% at the protein level, an important residual Ca 2+ entry persisted upon store depletion. Such a "partial" SOCE reduction was already observed, for instance in smooth muscle cells [52][53][54] or HEK cells [20], but in most cell types, the inhibition of SOCE upon STIM1 invalidation is very pronounced [3,39,55,56]. This finding prompted us to investigate the mechanism of the residual TG-induced Ca 2+ entry.…”
Section: Discussionmentioning
confidence: 74%
“…Interestingly, even though the silencing efficiency was of between 65 and 80% at the protein level, an important residual Ca 2+ entry persisted upon store depletion. Such a "partial" SOCE reduction was already observed, for instance in smooth muscle cells [52][53][54] or HEK cells [20], but in most cell types, the inhibition of SOCE upon STIM1 invalidation is very pronounced [3,39,55,56]. This finding prompted us to investigate the mechanism of the residual TG-induced Ca 2+ entry.…”
Section: Discussionmentioning
confidence: 74%
“…Ca 2+ influx through SOCE involves keeping a sustained high Ca 2+ concentration in the Ca 2+ stores and refilling the SR when it releases Ca 2+ . SOCE was shown to be upregulated in proliferating porcine bronchial smooth muscle cells, aortic smooth muscle cells, and pulmonary artery smooth muscle cells (Sweeney et al 2002;Lu et al 2009;Berra-Romani et al 2008). Our data suggest that SOCE activity contributes to mesangial cell proliferation and that decreased SOCE contributed to a lower proliferation rate in GMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies suggested that this activation is governed by up-regulation of TRP channels [196,197] while others localized the ER as the target-site [198][199][200][201][202].…”
Section: Hypoxia Effects On Soce and Crac/orai Channelsmentioning
confidence: 99%
“…Lu et al proposed that SOCE activation by hypoxia is via STIM1 while STIM2 played no significant role in this context [200]. Conversely, Berna-Erro et al [201] reported that STIM2 is essential for the hypoxia induced Ca 2+ overload, while manipulations of STIM1 expression had no significant effect.…”
Section: Hypoxia Effects On Soce and Crac/orai Channelsmentioning
confidence: 99%